Direct and indirect effects of elevated atmospheric CO2 on net ecosystem production in a Chesapeake Bay tidal wetland. (11th September 2013) - Erickson, John E.; Peresta, Gary; Montovan, Kathryn J.; Drake, Bert G.
Abstract The rapid increase in atmospheric CO2 concentrations (Ca) has resulted in extensive research efforts to understand its impact on terrestrial ecosystems, especially carbon balance. Despite these efforts, there are relatively few data comparing net ecosystem exchange of CO2 between the atmosphere and the biosphere (NEE), under both ambient and elevated Ca. Here we report data on annual sums of CO2 (NEEnet) for 19 years on a Chesapeake Bay tidal wetland for Scirpus olneyi (C3 photosynthetic pathway)‐ and Spartina patens (C4 photosynthetic pathway)‐dominated high marsh communities exposed to ambient and elevated Ca (ambient + 340 ppm). Our objectives were to (i) quantify effects of elevated Ca on seasonally integrated CO2 assimilation (NEEnet = NEEday + NEEnight, kg C m−2 y−1) for the two communities; and (ii) quantify effects of altered canopy N content on ecosystem photosynthesis and respiration. Across all years, NEEnet averaged 1.9 kg m−2 y−1 in ambient Ca and 2.5 kg m−2 y−1 in elevated Ca, for the C3‐dominated community. Similarly, elevated Ca significantly (P < 0.01) increased carbon uptake in the C4‐dominated community, as NEEnet averaged 1.5 kg m−2 y−1 in ambient Ca and 1.7 kg m−2 y−1 in elevated Ca. This resulted in an average CO2 stimulation of 32% and 13% of seasonally integrated NEEnet for the C3‐ and C4‐dominated communities, respectively. Increased NEEday was correlated with increased efficiencies of light and nitrogen use for net carbon assimilation under elevated Ca, while decreased NEEnight was associated with lower canopy nitrogen content. These results suggest that rising Ca may increase carbon assimilation in both C3‐ and C4‐dominated wetland communities. The challenge remains to identify the fate of the assimilated carbon.